The Influence of Flash Card Learning Media toward Students’ Writing Skill of Explanatory Text - Wardiah, Dessy; Lepiana, Lia Juniarsih (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis study aimed at finding out the influence of flash card learning media toward students? writing skill of explanatory text. There were 72 students which 36 experimental class students (XI.TAV.1) and 36 control class students (XI.TITL.2). This research was a quantitative experimental design. The data were collected by using test and documentation. The results of data analysis using the t-test formula obtained t-count = 11.48, and t-table with a real level of 5% and dk = 70 obtained t-table = 1.668. Thus, it turns out that t-count> t-table (I-?) (11.48> 1.668). So, the hypothesis was accepted. This proves that the learning outcomes of writing explanatory text using Flash Card learning media is more influential.Keywords: Flash Card Learning Media; Students? Writing Skill; Explanatory Text.